Quality criteria of best practice for the implementation of ICT – level institution - Ferreiro Gravie, Ramón F. (Revista Complutense de Educación, 2012)
The article presents a list of criteria of quality for best practice in the application of ICTs in Latin American institutions. Reflection is done based on the results of a inquiry to experts in school courses 2008-2009 and 2009-2010 among teachers, researchers and leaders of education of Latin America and the Caribbean. Responses, comments and suggestions allowed the preparation of a working paper as exploratory evidence still undergoing experimental study on new learning environments.
Keywords: Practices; ICT; Distance Education; New Learning Environments